The effect of cold work treatment on the formation of titanium dioxide by thermal electrochemical anodizing of TI-6AL-4V [electronic resource] - Ooi, Chun Wei, 1987-; Dadan Ramdan, supervisor; Fakulti Kejuruteraan Mekanikal (2011)
Project Paper (Sarjana Muda Kejuruteran (Mekanikal - Bahan)) - Universiti Teknologi Malaysia, 2011